World Development Indicators 2013 (World Bank e-Library., 2013)
World Development Indicators (WDI) is the World Bank?s premier annual compilation of data about development. Compiled from officially-recognized international sources, WDI presents the most current and accurate global development data available, including national, regional and global estimates. This year?s print edition and e-book have been redesigned to allow users the convenience of easily linking to the latest data on-line. What you will find in the print edition: ? A selection of the most popular indicators across 155 economies and 14 country groups organized into six WDI themes ? Thematic and regional highlights, providing an overview of global development trends ? An in-depth review of the progress made toward achieving the Millennium Development Goals ? A user guide describing resources available on-line and on mobile apps. What you can do on-line: ? Download individual tables and other key information ? Access and download time series data using the data retrieval system ? Access indicators in five different languages (Arabic, Chinese, French, English, and Spanish) ? Directly obtain the the most up-to-date data available. The WDI Little Data Book 2013 is a companion to the WDI, and is a handy country-by-country view of key development indicators for more than 200 countries. Each page provides a country data profile of of its people, environment, economy, states and markets, and global links.. ACCESS WDI TIME SERIES DATA FREE ONLINE = data.worldbank.org (the full data retrieval system organized by indicator, country and topic); and data.worldbank.org/data-catalog/world-development-indicators (for all on-line WDI resources) DOWNLOAD THE WDI DATAFINDER MOBILE APP AND OTHERS = data.worldbank.org/apps WDI DataFinder is a mobile app for browsing the current WDI database on smartphones and tablets, using iOS, Android, and Blackberry, available in four languages: English, French, Spanish, and Chinese. Use the app to browse data using the structure of the WDI; visually compare countries and indicators; create, edit and save customized tables, charts and maps; and share what you create on Twitter, Facebook, and via email.